Institutionalization, Universalism and Prospects for the Development of Accounting Knowledge - N. A. Mislavskaya (Учёт. Анализ. Аудит)
The current stage of development of the domestic accounting system and accounting (financial) statements is characterized by a distortion of the essence of the social institution of accounting knowledge. The latter implies the existence and functioning of the two parity components — science as the evolving system of knowledge aimed at obtaining objectively structured and reasonable information about economic reality, as well as science as the sphere of activity of the professional economic community. Moreover, the first component, in accordance with the tenets of the science studies, is given the dominant, guiding role, which focuses the attention of practical activity on the goals and objectives of the society. Reforming accounting in accordance with international financial reporting standards led to the prevalence of the regulatory paradigm (practical component), which set a certain framework for the development of scientific thought, and in the future could lead to full discrimination of the social institution of accounting. The target setting of this article is aimed at identifying the underlying causes of the problems of institutionalization of the national accounting system. The substantiation of the author’s point of view required a system analysis of the results of scientific studies of sociology, philosophy and ethics of science, extrapolation of the knowledge gained to the object and subject of accounting. The formulation of conclusions predetermined the use of such general scientific research methods as observation, evaluation, deduction, and intellectual modeling. The results of the relevant studies actualize the need for large-scale research in the field of ethics of accounting science, as a primary element of the institutionalization process. The necessity for the development of academic ethics in accordance with the principle of mediated universalism is proved. The directions of development of accounting and accounting (financial) reporting are predicted — unipolarization, multi-polarization, non-polarization.